Taking Charge after Stroke: A randomized controlled trial of a person-centered, self-directed rehabilitation intervention. Issue 9 (December 2020) - Fu, Vivian; Weatherall, Mark; McPherson, Kathryn; Taylor, William; McRae, Anna; Thomson, Tom; Gommans, John; Green, Geoff; Harwood, Matire; Ranta, Annemarei; Hanger, Carl; Riley, Judith; et al.
Background and purpose: "Take Charge" is a novel, community-based self-directed rehabilitation intervention which helps a person with stroke take charge of their own recovery. In a previous randomized controlled trial, a single Take Charge session improved independence and health-related quality of life 12 months following stroke in Māori and Pacific New Zealanders. We tested the same intervention in three doses (zero, one, or two sessions) in a larger study and in a broader non-Māori and non-Pacific population with stroke. We aimed to confirm whether the Take Charge intervention improved quality of life at 12 months after stroke in a different population and whether two sessions were more effective than one. Methods: We randomized 400 people within 16 weeks of acute stroke who had been discharged to institution-free community living at seven centers in New Zealand to a single Take Charge session (TC1, n = 132), two Take Charge sessions six weeks apart (TC2, n = 138), or a control intervention (n = 130). Take Charge is a "talking therapy" that encourages a sense of purpose, autonomy, mastery, and connectedness with others. The primary outcome was the Physical Component Summary score of the Short Form 36 at 12 months following stroke comparing any Take Charge intervention to control. Results: Of the 400 people randomized (mean age 72.2 years, 58.5% male), 10 died and two withdrew from the study. The remaining 388 (97%) people were followed up at 12 months after stroke. Twelve months following stroke, participants in either of the TC groups (i.e. TC1 + TC2) scored 2.9 (95% confidence intervals (CI) 0.95 to 4.9, p = 0.004) points higher (better) than control on the Short Form 36 Physical Component Summary. This difference remained significant when adjusted for pre-specified baseline variables. There was a dose effect with Short Form 36 Physical Component Summary scores increasing by 1.9 points (95% CI 0.8 to 3.1, p < 0.001) for each extra Take Charge session received. Exposure to the Take Charge intervention was associated with reduced odds of being dependent (modified Rankin Scale 3 to 5) at 12 months (TC1 + TC2 12% versus control 19.5%, odds ratio 0.55, 95% CI 0.31 to 0.99, p = 0.045). Conclusions: Confirming the previous randomized controlled trial outcome, Take Charge—a low-cost, person-centered, self-directed rehabilitation intervention after stroke—improved health-related quality of life and independence. Clinical trial registration-URL: http://www.anzctr.org.au . Unique identifier: ACTRN12615001163594